BAIT PREFERENCES BY DIFFERENT SMALL MAMMAL ASSEMBLAGES FOR EFFECTIVE CAGE-TRAPPING - Mohd-Taib, Farah Shafawati; Ishak, Siti Nabilah (Malaysian Journal of Science, 2021)
The ecological study of small mammals often uses the cage-trapping method, installed with baits. Capture rates vary according to different baits used. We want to determine the bait preferences by different small mammal groups. The cage-trapping approach used common domestic bait types available, namely, aromatic banana, sweet potato with peanut butter, oil palm fruit, dried salted fish, jackfruit, and roasted coconut flesh. Sampling was conducted in three different habitat categories, namely urban, semi-urban, and recreational forests, located in Selangor, Malaysia, for one year. A total of 537 small mammals from 15 species were sampled, which was then grouped into seven groups (i.e., Rattus sp., Maxomys sp., Sundamys sp., Leopaldamys sabanus, Suncus murinus, squirrels, and Tupaia glis). Bait preferences were significantly different among the different small mammal groups, i.e., F (6,35) = 5.621, p = 0.000, with bananas shown to be most preferred bait, followed by oil palm fruits and sweet potatoes. Non-metric multidimensional scaling (nMDS) analysis revealed that the Rattus species encompassed the most diverse bait preference, while S. murinus and L. sabanus were the most selective. Muridae preferred sweet potatoes with peanut butter over bananas, while Sciuridae and Tupaiidae preferred bananas, and Soricidae preferred dried salted fish. This study elucidates the most effective bait selection for different small mammal assemblages, serving as a guide to increase capture rates when sampling targeted population of small mammals. Apart from that, it is helpful for effective rodent pest control.